2020
DOI: 10.1038/s41598-020-75504-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics and physics of a glass/particles photonic sponge

Abstract: A glass containing mechanoluminescent crystalline particles behaves as a photonic sponge: that is to say it fills up with trapped electrons when exposed to UV light, and it emits light when submitted to a mechanical loading, similar to a sponge soaked with water that is wringed under mechanical action! A major finding of the present study is that the elasto-mechanoluminescence effect showing up on unloading is governed by the deviatoric part of the applied stress (no effect under hydrostatic pressure). Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Under such a stress profile, the ML intensity was found to decay with time yet at a rate which is faster than that of the stress‐free persistent luminescence under the same charging conditions. [ 215,219,220,222,223 ] This decaying trend of ML under constant load has been detected in ML phosphors other than SrAl 2 O 4 :Eu 2+ as well, such as (Ba,Ca)TiO 3 :Pr 3+ , [ 224 ] BaSi 2 O 2 N 2 :Eu 2+ , [ 225 ] (Ca,Sr)Al 2 Si 2 O 8 :Eu 2+ ,Pr 3+ , etc. [ 226 ] Furthermore, for a repetitive triangular stress profile, the ML intensity at the maximum stress decreases with increasing cycling number N but can restore to the initial value ( N = 1) after sufficient optical charging.…”
Section: Phenomena Related To Trapping and Energy Storagementioning
confidence: 89%
See 4 more Smart Citations
“…Under such a stress profile, the ML intensity was found to decay with time yet at a rate which is faster than that of the stress‐free persistent luminescence under the same charging conditions. [ 215,219,220,222,223 ] This decaying trend of ML under constant load has been detected in ML phosphors other than SrAl 2 O 4 :Eu 2+ as well, such as (Ba,Ca)TiO 3 :Pr 3+ , [ 224 ] BaSi 2 O 2 N 2 :Eu 2+ , [ 225 ] (Ca,Sr)Al 2 Si 2 O 8 :Eu 2+ ,Pr 3+ , etc. [ 226 ] Furthermore, for a repetitive triangular stress profile, the ML intensity at the maximum stress decreases with increasing cycling number N but can restore to the initial value ( N = 1) after sufficient optical charging.…”
Section: Phenomena Related To Trapping and Energy Storagementioning
confidence: 89%
“…Xu et al [201] identified a linear relationship between ML intensity and stress during a ramp. Kim et al [218] confirmed this relation but showed that only the effective stress (namely von Mises stress) contributes to ML, while Dubernet et al [219] argues that hydrostatic stress also causes ML from SrAl 2 O 4 :Eu 2+ particles embedded in a glass matrix. In contrast, Rahimi et al [220] found a quadratic relationship between ML intensity and stress.…”
Section: Mechanoluminescencementioning
confidence: 97%
See 3 more Smart Citations